Persepsi Mahasiswa Pendidikan Matematika Terkait Sistem Pembelajaran di Masa Transisi Era Pandemi dan New Normal - Ulfa Lu'luilmaknun; Nilza Humaira Salsabila (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2022)
This study aims to investigate the perceptions of mathematics education students related to the transition of online learning in pandemic era to blended learning in new normal era. The subjects of this study were 44 students of mathematics education department in academic year 2021/2022 in Mataram University. The research method implemented was descriptive qualitative. The data collection technique used questionnaires. The data in this study were analysed using statistics. Based on the findings, there were 50% of students selected full offline learning, 16% of students selected full online learning, and 34% of students selected blended learning. There were 61% of students considered that full online learning was sometimes effective, however 30% of them considered that it was ineffective, and 9% considered it effective. There were 42% of students stated that online learning was appropriate to be implemented in the learning materials related to education, 17% stated that it was appropriate to be implemented in the learning materials related to mathematics, 29% stated that there was no appropriate materials, and 12% stated that every material was suitable to implemennt online learning. It can be concluded that onlne learning is effective if it is combined with offline learning as a blended learning.